KARAKTERISTIK PERKEMBANGAN STRUKTUR RUANG IBU KOTA KECAMATAN GEMOLONG KABUPATEN SRAGEN - Setiawan, Dhoni; Rahdriawan, Mardwi (Jurnal Pengembangan Kota, 2014)
City is a space that serves as a center place of activities, over time the city was experiencing growth and development, both physical and non-physical conditions. So these conditions affect the change in the pattern of land use, activity system as well as the pattern of people and goods mobility that are happening in the urban system. The phenomenon of the emergence of new urban areas (cities and towns) in IKK Gemolong causes changes in land use patterns along the road corridor is experiencing rapid development, it is evidenced by the increased activity and physical growth of the city. The conditions were observed with the growth of new activities such as residential, commercial district and other commercial areas. So that it will affect land use patterns, activities systems and people and goods mobility patterns that occur, which in turn will affect the characteristics of the spatial structure of the development of IKK Gemolong formed as a town in Sragen. The focus of discussion such as land use, population activity systems, as well as the people and goods mobility which the influencing factors of the formation of the spatial structure of a city. The study is considered important because as the basis for consideration in the development of towns in the future. This is because the policy of urban development continues in administrative and sectoral nature, so the presence of the regional autonomy policy of development with regional and integrated system and assessed more quickly to implement. This study used quantitative an quantitative study method. The analysis results indicated the characteristics of land use in Gemolong dominated by settlements, while the commercial district developed along the main streets of this town because Gemolong have function as service centers for its surrounding areas. The residents of Gemolong mostly have work in the non-agricultural sectors, such as trade and services, while the population as a farmer is relatively small, so that these conditions indicated that Gemolong says as urban area. The people mobility in Gemolong originated from both internal and external area of the town in destination location of commercial areas to have studying, working, shopping and other purposes. The residents of Gemolong do not have to big cities to access the daily life necessities for since it is already available in Gemolong. Based on the phenomenon of Gemolong have a compact city type of development, while the structure of urban spaces that were formed have view more functioning of each of the regions even though the condition is still occurring mixture of functions. Then, the structure of urban spaces is the type of sector, although not as ideal as yet which happened in developed countries.